Impact of Neutropenia on Clinical Outcomes after Lung Transplantation - Raquel Sanabrias Fernández de Sevilla; Ana Concepción Sánchez Cerviño; Rosalía Laporta Hernández; Myriam Aguilar Pérez; Christian García Fadul; Sarela García-Masedo Fernández; Amelia Sánchez Guerrero; María Piedad Ussetti Gil (Medical Sciences)
Background/Objectives: Neutropenia is a frequent complication among solid organ transplant (SOT) recipients receiving immunosuppressive therapy and antimicrobial prophylaxis. However, there are limited studies analysing the frequency and impact of neutropenia in lung transplant recipients (LTRs). Our aim was to analyse the frequency of neutropenia, the need for granulocyte colony-stimulating factor (GCSF) treatment within the first 18 months post-transplant and its association with acute rejection, chronic lung allograft dysfunction (CLAD), overall survival and the development of infections. Methods: This observational and retrospective study recruited 305 patients who underwent lung transplantation between 2009 and 2019, with outpatient quarterly follow-up during the first 18 months post-surgery.Results: During this period, 51.8% of patients experienced at least one episode of neutropenia. Neutropenia was classified as mild in 50.57% of cases, moderate in 36.88% and severe in 12.54%. GCSF treatment was indicated in 23.28% of patients, with a mean dose of 3.53 units. No statistically significant association was observed between neutropenia or its severity and the development of acute rejection, CLAD or overall survival. However, the patients who received GCSF treatment had a higher mortality rate compared to those who did not. Sixteen patients (5.25%) developed infections during neutropenia, with bacterial infections being the most common. Conclusions: Neutropenia is common in the first 18 months after lung transplantation and most episodes are mild. We did not find an association between neutropenia and acute rejection, CLAD, or mortality. However, the use of GCSF were associated with worse post-transplant survival.